Implementasi Manajemen Kelas Berdasarkan Nilai-Nilai Akhlakul Karimah - Ahmad Aly Syukron Aziz Al Mubarok (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2023)
Classes as student environments and study groups need to be managed to achieve educational goals, and management can also be in the form of managing learning and grouping students in a class. Moral education for students aims to make students strong Muslim individuals through the habituation of akhlaqul karimah and instilling a spirit of leadership in the ongoing educational process. In order for the implementation of moral education to run smoothly, the implementation of these habits must be managed properly. Classes as student environments and study groups need to be managed so that the management of educational goals is achieved. can also be a means of managing learning and in the form of grouping students in class. The values ​​of Akhlakul Karimah are the beliefs held by a Muslim and are reflected in his behavior, speech or behavior in relating or socializing with the surrounding community, with the aim that everyone has good morals (morals) has good sharia. good. behavior or habits. One aspect that must be considered in education is morals/character, namely the values ​​of human behavior in relation to Allah SWT, oneself, fellow human beings and the environment. With the rampant moral crisis, these character values ​​are then manifested through the habituation of akhlakul karimah to achieve national education goals. In order to maintain an environment that does not violate Shari'a, Madrasas and teachers make classroom management by